The Relationship between Husband's Support and Parenting Stress in Mothers with Children with Special Needs - Fitri Ayu Kusumaningrum; Egha Sulistyorini Larasati (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
This study aims to determine the relationship between husband's support and parenting stress in mothers who have children with special needs. The subjects involved in this study were 85 mothers who have children with special needs. Data collection used the Spouse Support scale [1] and the Parental Stress Scale [2]. Data analysis used the Spearman's Rho correlation technique which showed that there was a negative relationship between husband's support and parenting stress in mothers who have children with special needs. This was revealed based on the value of r = -0.312 and p = 0.002 (p < 0.05). The results of this study were accepted.